The influence of intelligence factors on the auditors performance at public accounting firms in Jakarta area - Syafira Nida Isyarani; Christina Dwi Astuti (Institute of Computer Science (IOCS), 2023)
This study examines the influence of Intelligence Factors on Auditor Performance at Public Accounting Firms in Jakarta Region. The independent variables used in this study involve Intellectual Intelligence, Spiritual Intelligence, Emotional Intelligence, and Adversity Intelligence. Meanwhile, the dependent variable used in this study is Auditor Performance. This research is a type of quantitative research. The data collection method used a questionnaire. The population used in this study are the auditors working in Public Accounting Firms in Jakarta. The sampling technique in this study used a purposive sampling method with a total of 312 samples. In addition, the data analysis method used in this research is the tests of descsriptive statistics, data quality, multiple linear regression, and hypothesis testing. Based on the analysis obtained from this study, it is concluded that Intellectual Intelligence, Spiritual Intelligence, Emotional Intelligence, and Adversity Intelligence positively influence Auditor Performance